First-principle study of interstitial atoms (C, B and Si) in CrFeCoNi high entropy alloy. (June 2022) - Song, Hongquan; Yu, Mengge; Zhang, Yunli; Zhang, Wei; Liu, Zhijie; Zhang, Fuxiang; Tian, Fuyang
Abstract: The incorporation of nonmetallic elements in alloys is one of the major approaches to tailor properties. In this paper, first-principles methods are employed to investigate the effect of interstitial C, B and Si in CrFeCoNi high entropy alloys (HEAs). The four local environments around interstitial atom, i.e., Cr-rich, Fe-rich, Co-rich and Ni-rich have the close formation energy for each interstitial atom. The bond length between the interstitial atom and alloying component suggests the severe lattice distortion occurs, even in Si doped case. Whereas the local magnetic moments of Ni are not affected by the interstitial atoms. Graphical Abstract: ga1